A Brief Survey of the House Allocation Problems - Tapkı, İpek Gürsel; Selçuk, Elif Akben (Games Review, 2017)
The objective of this paper is to briefly review house allocation problems. We first give the definition and the aim of the mechanism design theory. Next we discuss its applications to markets with no monetary transfer, such as house allocation, kidney exchange and school choice. We review the literature for (i) house allocation problems, (ii) house allocation problems with existing tenants, and (iii) house allocation problems with existing tenants and newcomers.